World literature and dissent - Burns, Lorna; Muth, Katie (Routledge, 2019)
"World Literature and Dissent reconsiders the role of dissent in the contemporary aesthetics of globalisation. Bringing together scholars from postcolonial and world literatures, the collection addresses themes of knowledge and the epistemology of ignorance, the rhetoric of innocence and enchantment, translation and global justice, and the aesthetics of revolution. The essays reframe the field of contemporary world literature in relation to dissenting politics and aesthetics, asking how we might theorise a world literature that cultivates radical thought and supports uncompromising resistance to the apparatuses of global inequality, furthers social justice and values human expression." --